Enhancing UX Design Through Eye-Tracking and Image Processing: Practical Insights and Applications - Baharum A.; Ismail R.; Halamy S.; Rahim E.A.; Noor N.A.M.; Deris F.D. (Institute of Electrical and Electronics Engineers Inc., 2025)
In the digital age, optimizing user experience (UX) is paramount for the success of various applications and interfaces. Eye-tracking, a method used to monitor and analyze eye movements, has emerged as a powerful tool in UX research. This study investigates the intersection of eye-tracking and image processing, focusing on how insights derived from eye-tracking data can enhance UX design. Through a series of case studies, this research explores the practical applications of eye-tracking in improving user interaction with image-based interfaces. By analyzing user attention patterns, gaze fixation durations, and visual engagement metrics, the study uncovers valuable insights into user behaviour and preferences. These insights inform design decisions related to interface layout, content placement, and visual hierarchy, ultimately leading to more intuitive and engaging user experiences. The findings from this study provide practical guidelines and best practices for integrating eye tracking into the UX design process, offering valuable insights for designers, developers, and researchers seeking to optimize user interaction with image-based applications and interfaces. ? 2024 IEEE.